2021
DOI: 10.1371/journal.pone.0252376
|View full text |Cite
|
Sign up to set email alerts
|

Shifting networks and mixing metals: Changing metal trade routes to Scandinavia correlate with Neolithic and Bronze Age transformations

Abstract: Based on 550 metal analyses, this study sheds decisive light on how the Nordic Bronze Age was founded on metal imports from shifting ore sources associated with altered trade routes. On-and-off presence of copper characterised the Neolithic. At 2100–2000 BC, a continuous rise in the flow of metals to southern Scandinavia begins. First to arrive via the central German Únětician hubs was high-impurity metal from the Austrian Inn Valley and Slovakia; this was complemented by high-tin British metal, enabling early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 70 publications
3
45
0
1
Order By: Relevance
“…As pointed out in previous studies, the mining and smelting areas in North Italy had a dominant supply role for the whole of Italy and parts of the Eastern Mediterranean during the Late Bronze Age [105,106,115]. Recent studied have also demonstrated that copper from these regions was traded even to North Europe [28,116].…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…As pointed out in previous studies, the mining and smelting areas in North Italy had a dominant supply role for the whole of Italy and parts of the Eastern Mediterranean during the Late Bronze Age [105,106,115]. Recent studied have also demonstrated that copper from these regions was traded even to North Europe [28,116].…”
Section: Discussionmentioning
confidence: 90%
“…Zn was below the detection limit of 0.1% in all samples, which was due the spectral interference with copper. Sulfur was not measured [28].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations